2020
DOI: 10.1017/s1092852920001807
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month follow-up study on response and relapse rates following an acute trial of repetitive transcranial magnetic stimulation in patients with major depression

Abstract: Background Little is known about the post-acute effects of repetitive transcranial magnetic stimulation (rTMS) in patients with major depression. The present study focused on the 6-month follow-up of a sample of patients with major depression, after the completion of an acute 4 weeks rTMS trial, with the aim of evaluating response (in terms of sustained and late response) and relapse rates. Methods Following the completion of an acute trial of rTMS (T0-T4), 31 drug-resistant depressed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…It has been noted that the antidepressant effects of TMS were not limited to the acute treatment period, but a considerable number of patients (up to 63%) showed a response even weeks or months after. Additionally, post-acute treatment relapse risk was very low in the first month [19]. In this context, maintenance starting before this period and close to acute treatment could overlap with active protocol efficacy, hence suggesting a possible superfluous treatment.…”
Section: Temporal Distance From Acute To Maintenance Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that the antidepressant effects of TMS were not limited to the acute treatment period, but a considerable number of patients (up to 63%) showed a response even weeks or months after. Additionally, post-acute treatment relapse risk was very low in the first month [19]. In this context, maintenance starting before this period and close to acute treatment could overlap with active protocol efficacy, hence suggesting a possible superfluous treatment.…”
Section: Temporal Distance From Acute To Maintenance Protocolmentioning
confidence: 99%
“…A recent study on this matter pointed out that a significant portion of patients (up to 63%) does not respond to acute rTMS protocols immediately but rather shows a delayed response [19]. This finding suggests that the mechanisms underlying magnetic stimulation are complex and involve changes that occur over time.…”
Section: Introductionmentioning
confidence: 99%
“…Arici et al reported that after rTMS treatment of patients with MDD for a total of 20 sessions over 4 weeks, 90% of those who responded remained responsive during a 6-month follow-up period [ 44 ]. According to meta-analysis of the durability of rTMS, high-frequency rTMS had a slight antidepressant effect at short-term follow-up [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the follow-up periods were short, ranging from 3 weeks to 3 months. In a follow-up study of standard TMS for depression, a good antidepressant effect was still observed at 6 months [ 44 , 55 ]. ATMS appears to have similar long-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Arici et al found that after rTMS treatment of patients with MDD for a total of 20 sessions over 4 weeks, 90% of those who responded remained responsive during a 6-month follow-up period [21]. The metaresults on the durability of repetitive transcranial magnetic stimulation also showed that high-frequency rTMS continued to have a small antidepressant effect at short-term follow-up [22].…”
Section: Sustained Effects Of Atms In Patients With Mddmentioning
confidence: 99%